Development and validation of a questionnaire to predict intention to comply to iron supplement during pregnancy - Raudah Abd Rahman; Idayu Badilla Idris; Zaleha Md Isa; Rahana Abd Rahman (Penerbit Universiti Kebangsaan Malaysia, 2021)
The World Health Organisation (WHO) has recommended iron supplementation to overcomeanaemia in pregnancy. In Malaysia, about half of pregnant women with anaemia do notcomply to iron supplement. The purpose of this study is to develop and validate aquestionnaire that assesses the attitude towards iron supplementation and later to predictintention to comply with daily iron supplement among pregnant women. Based on theguidelines for construction of the Theory of Planned Behaviour questionnaire, 18 items werecreated initially by using the findings from an open-ended questionnaire survey, literaturereviews and experts’ opinion. From content validity by 3 experts, 15 items with contentvalidity ratio (CVR) of ≥0.99 were retained. From a pilot test for exploratory factor analysis(EFA), total of 12 items were retained, and classified into 3 components and termed as“Attitudes”, “Subjective Norms” and “Perceived Behaviour Control”. Cronbach Alpha for the12 items was 0.814, and for each component were 0.844, 0.813 and 0.901 respectively, whichindicates acceptable internal consistency. During the Confirmatory Factor Analysis (CFA), afinal 10 items were retained. The construct validity was good where the Fitness Index haveachieved the threshold i.e. p-value >0.05, RMSEA <0.08, CFI >0.90 and the ChiSq/df ratio<3.00. The convergent validity and composite reliability were good i.e. Average VarianceExtracted (AVE) ≥0.50, and Composite Reliability (CR) ≥0.60 respectively. As a conclusion,the validation of this newly developed questionnaire has shown promising result andpotentially reliable in predicting compliance to iron supplement among pregnant womenspecifically in Malaysia.